2012
DOI: 10.1007/s10021-012-9521-7
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic N Deposition Increases Soil C Storage by Decreasing the Extent of Litter Decay: Analysis of Field Observations with an Ecosystem Model

Abstract: Recent meta-analyses of experimental studies simulating increased anthropogenic nitrogen (N) deposition in forests reveal greater soil carbon (C) storage under elevated levels of atmospheric N deposition. However, these effects have not yet been included in ecosystem-scale models of soil C and N cycling and it is unclear whether increased soil C storage results from slower decomposition rates or a reduced extent of decomposition (for example, an increase in the amount of litter entering slowly decaying humus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 71 publications
5
29
2
Order By: Relevance
“…Meanwhile, the leaf litter N concentration has increased by 25%, and inorganic N concentrations in the forest floor have increased by 288% (3,5). With the use of field observations and a biogeochemical simulation model, we further determined that chronic N deposition has decreased the extent of microbial decay, thereby leading to an accumulation of soil organic matter (6). In combination, these observations indicate that a microbial mechanism underlies a decline in litter decay under experimental N deposition, which has enhanced soil C storage (ϩ10%) (3,7).…”
mentioning
confidence: 99%
“…Meanwhile, the leaf litter N concentration has increased by 25%, and inorganic N concentrations in the forest floor have increased by 288% (3,5). With the use of field observations and a biogeochemical simulation model, we further determined that chronic N deposition has decreased the extent of microbial decay, thereby leading to an accumulation of soil organic matter (6). In combination, these observations indicate that a microbial mechanism underlies a decline in litter decay under experimental N deposition, which has enhanced soil C storage (ϩ10%) (3,7).…”
mentioning
confidence: 99%
“…A three-years of N addition experiment suggested that N addition increased root and shoot biomass by 37 and 23%, respectively, without significant impact on decomposition, causing the increase in soil C by approximately 15% [80]. Other researches related to the response of plant community structure to N addition have suggested the negative influences on plant community and richness, possibly due to the acidifying effect of nitrogen increase [59,69,75]. Since soil enzyme activity and microbial community compositions influencing nutrient transformation between soil and plants, the studies on their responses to nitrogen input can be particularly important in understanding the underlying mechanisms of nutrient cycles.…”
Section: Soil Biologymentioning
confidence: 99%
“…N input can promote or inhibit the rate and extent of soil organic matter decomposition through changing the activity and composition of microbial community (DeForest et al 2004), as well as the chemical property of organic matter (e.g., C/N, lignin/N, alkyl C/O-alkyl C) (Whittinghill et al 2012). Along with the continuous N input, NO 3 − and NH 4 + ions are rapidly assimilated by plants and soil microbes; subsequently, the N input stimulates soil microbial activity and decreases litter's C/N ratio leading to increases in litter decay and soil CO 2 emission (Knorr et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In some grassland and forest ecosystems, low level of N addition increases litter return and stimulates soil microbial activity because it satisfies the N demand of soil microorganisms to decompose the relatively small pool of available labile C substrates with low N contents (Fang et al 2014b); however, high level of inorganic N inputs suppresses the synthesis of lignolytic enzymes by some fungi due to the decrease in organic matter decay extent (Cusack et al 2011;Whittinghill et al 2012). Also, because NO 3 − assimilated by plants and microbes has to be firstly reduced to NH 4 + , this energy-intensive process consumes more C fixed by photosynthesis and releases additional CO 2 (Gavrichkova and Kuzyakov 2008;Tischner 2000).…”
Section: Introductionmentioning
confidence: 99%